The Effect of Talent Development on the Health Sector performance in the County Government of Bungoma. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In today’s competitive and dynamic business environment, organizations must invest in talent development to remain innovative, productive, and adaptable to change. This involves activities such as training, coaching, mentoring, performance management, career planning, and leadership development. Many organizations face many challenges related to talent development increased job dissatisfaction, retention, and organizational growth. These challenges undermine employee performance in public health facilities in Bungoma County. The primary aim of this research was to establish the effect of Talent Development on Health Sector performance in the County Government of Bungoma, Kenya. The research was guided by the Theory on Talent Development which was conducted among the Health Sector staff in the County Government of Bungoma. This research employed a descriptive survey research design, analysing data through descriptive statistics, including mean, standard deviation, frequency, and percentage, as well as inferential statistics, comprising Pearson correlation and regression analysis, given in tabular form the target population of 240 respondents was drawn from the County Referral Hospital and 9 Sub-County Hospitals. Simple random sampling was used to select 15 Heads of Ward Sections while census method was adopted in selecting 94 respondents within the Ministry of Health to give a total of 109 respondents as the sample size. The research incorporated primary data sources collected using closed and open-ended questionnaires and interviews, which were pretested in Turkana County to evaluate validity and reliability. Quantitative data collected through questionnaires were analysed using SPSS, while qualitative data from open-ended questions and interviews were subjected to thematic analysis. The findings indicated that all aspects of Talent Development exhibited a positive and significant correlation with Health Sector Performance in Bungoma County, Kenya. The results posited that Health Sector Performance increases by 0.335 units for each unit rise in Talent Development (β2=0.335, p<0.05). This outcome suggests that the County Government of Bungoma should employ talent development as it plays a crucial role in shaping the efficacy of healthcare performance through enhanced competencies and expertise of healthcare professionals